2014
DOI: 10.5935/0004-2749.20140077
|View full text |Cite
|
Sign up to set email alerts
|

Use of impression cytology for the detection of unsuspected ocular surface squamous neoplasia cells in pterygia

Abstract: Purpose: To evaluate the agreement between the methodologies of impression cytology (IC) and histopathology regarding epithelial lesions clinically diagnosed as pterygium and also regarding the detection of unsuspected and associated ocular surface squamous neoplasia (OSSN). Methods: Thirty-two Brazilian patients were included and IC was performed on all pterygia before excision. Histopathogical examination was considered the gold standard and was performed by two experienced ocular pathologists in which conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…ICS and CBS provided samples with equal cell quality in healthy and diseased horses. In human ophthalmology, ICS is used for the diagnosis of ocular surface tumours as cells harvested with ICS are of highest quality [4,9,10,25]. In the current study, the 2 cases of SCC were identified with both ICS and CBS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…ICS and CBS provided samples with equal cell quality in healthy and diseased horses. In human ophthalmology, ICS is used for the diagnosis of ocular surface tumours as cells harvested with ICS are of highest quality [4,9,10,25]. In the current study, the 2 cases of SCC were identified with both ICS and CBS.…”
Section: Discussionmentioning
confidence: 91%
“…ICS collects the most superficial layers of the ocular surface due to the adhering property of the sampling device [4]. ICS is now widely used in human ophthalmology to examine the healthy ocular surface [5] and to assess conjunctival and corneal alterations in contact lens wearers [6][7][8] Examination of eyes with ocular surface neoplasia [9,10] and keratoconjunctivitis sicca [11,12] are other indications for ICS. A major advantage of ICS is the arrangement of harvested cells in their natural layout; thus enabling clinical pathologists to examine an exact copy of the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the question of using IC for the detection of OSSN in the setting of concomitant ocular surface disease requires further studies. Recently, Barros et al reported that IC demonstrated high agreement with the results of the histopathological analysis for detecting atypical epithelial cells from unsuspected OSSN in cases of pterygia from Brazil, showing unsuspected and associated OSSN cells in 13 specimens (40%) (41) . IC presents great advantages: (1) it provides a source of intact and well-preserved epithelial cells from the ocular surface in any type of ocular surface pathology; (2) it is a nonsurgical, easy-to-perform, quick, and inexpensive technique that can always be performed on an outpatient basis; (3) only topical anesthesia is required, and no side effects or contraindications have ever been noted and thus it can be applied to children; (4) repeated IC sampling in the same patient over time is an excellent way to demonstrate changes due to a certain event, to monitor the progress of a disease, or to follow the effect of a therapeutic intervention; (5) IC maintains cell-to-cell contacts, preventing the problems of EC or brush cytology, which may destroy much of the cell morphology, cause overlapping of cells, and hamper clear visualization of the in vivo arrangement of the cells; (6) IC samples can be processed using any type of microscopy in addition to polymerase chain reaction (PCR), immunoblotting analyses, and/or flow cytometry.…”
Section: Final Commentsmentioning
confidence: 61%
“…IC presents great advantages: (1) it provides a source of intact and well-preserved epithelial cells from the ocular surface in any type of ocular surface pathology; (2) it is a nonsurgical, easy-to-perform, quick, and inexpensive technique that can always be performed on an outpatient basis; (3) only topical anesthesia is required, and no side effects or contraindications have ever been noted and thus it can be applied to children; (4) repeated IC sampling in the same patient over time is an excellent way to demonstrate changes due to a certain event, to monitor the progress of a disease, or to follow the effect of a therapeutic intervention; (5) IC maintains cell-to-cell contacts, preventing the problems of EC or brush cytology, which may destroy much of the cell morphology, cause overlapping of cells, and hamper clear visualization of the in vivo arrangement of the cells; (6) IC samples can be processed using any type of microscopy in addition to polymerase chain reaction (PCR), immunoblotting analyses, and/or flow cytometry. Based on all these advantages, IC has become the technique of choice for sampling ocular surface epithelium for being a very useful research tool in both basic and clinical aspects (41)(42) . …”
Section: Final Commentsmentioning
confidence: 99%
“…McKelvie et al [5] have reported elastosis in 100% of their specimens, while a previous Brazilian study found elastosis in 81.4% [16]. In comparison, Tabrizi reported elastosis in 50% of the cases [17], whereas, Barros et al [18], observed elastosis in all pterygia.…”
Section: Discussionmentioning
confidence: 91%